The evolution of feedback practice of a mathematics teacher - Santos, Leonor (2012)
This study was done in the context of a project on learning assessment practices. It aims to understand the professional development of a math's teacher, regarding her practice in feedback production over a period of three years. Following an interpretive methodology, the data was collected from documents and interviews and the data analysis was done from pre-defined categories supported by the theoretical framework. This study shows that the teacher gives increased importance to feedback as a learning resource. Although she uses a standard feedback, her evolution points out to the establishment of favorable moments for student’s reflection, to noting fewer errors, encouraging correction and varying the feedback’s syntactic form